How the Incumbent Can Win: Managing Technological Transitions in the Semiconductor Industry - Iansiti, Marco (Management Science, 2000)
The paper reports on an empirical study of the management of technological transitions. It focuses on project-level mechanisms for the generation of knowledge through experimentation and for its accumulation through individual experience. It proposes a model that links these mechanisms to effectiveness in the management of revolutionary and evolutionary development approaches. This argument is tested with data describing projects conducted by all major competitors in the semiconductor industry. Each project was aimed at a technological transition, defined as the introduction of a major new generation of process technology. The analysis shows substantial differences among competitors in the approach taken (i.e., evolutionary vs. revolutionary) and results achieved. Additionally, it shows that individual organizations can migrate, over time, from evolution to revolution and vice versa. The analysis further indicates that accumulating experience and generating knowledge through experimentation are significantly associated with project performance. While product performance improvement through revolution is associated with research experience and with parallel experimentation capacity, improvement through evolution is associated with project experience and minimum experimental iteration time.